Data and codes for "Operating a contextual Stern-Gerlach apparatus" - Mavrogordatos, Themistoklis (Stockholm University, 2026)
We propose a contextual cavity/circuit QED analogue and extension of the Stern-Gerlach experiment, where the pseudo-spin of a two-state `atomic' transition plays the role of the ``spin'', while the resonant field driving the transition stands for the ``magnetic field''. A phase-sensitive continuous detection of the cavity field coupled to the induced `atomic' dipole affects the stability of the two distinct outcomes. The dressed states comprising the latter give their place to a self-consistent spontaneous dressed-state polarization as the driving strength is lowered. The associated evolution proves anew highly contextual, underpinned by a persistent production of coherent-state superpositions for a particular setting of the monitoring device. Finally, when bistability is absent, we employ the photoelectron `atomic' emission statistics as a diagnostic tool of the cavity field fluctuations.

The present dataset contains codes and data as MATLAB .m and .mat files, respectively. Data generated and used for each figure are grouped according to the figure order in the manuscript. For example, the folder FIG2/D300_pi_2 contains data collected for a drive amplitude ratio over dissipation rate equal to 300, and the local oscillator phase set to pi/2 in homodyne detection. As another example, the file titled Wss_30.mat contains the matrix data corresponding to the steady-state Wigner function of the cavity for a drive amplitude ratio over dissipation rate equal to 30, plotted in Fig. 3. For the same figure, the file titled, e.g., W23340.mat contains the matrix data corresponding to the conditioned Wigner function at the time t=(23340-1)*dt. The time step dt is set in the main code generating the individual trajectories.

The main MATLAB code used for generating quantum trajectories under homodyne (heterodyne) detection is Stern_Gerlach.m (Stern_Gerlach_het.m). A version for operation in the bad cavity limit is also included.
Keywords: Foundations of quantum mechanics; Quantum information, computation and communication; Quantum optics and quantum optomechanics; Subatomic Physics; Subatomär fysik